The propaganda of freedom : JFK, Shostakovich, Stravinsky, and the cultural cold war - Horowitz, Joseph, 1948- (Urbana : University of Illinois Press, 2023)
"Eloquently extolled by President John F. Kennedy, the idea that only artists in free societies can produce great art became a bedrock assumption of the Cold War. That this conviction defied centuries of historical evidence--to say nothing of achievements within the Soviet Union--failed to impact impregnable cultural Cold War doctrine. Horowitz shows how the efforts of the CIA-funded Congress for Cultural Freedom were distorted by an anti-totalitarian "psychology of exile" traceable to its secretary general, the displaced Russian aristocrat/composer Nicolas Nabokov, and to Nabokov's hero Igor Stravinsky. In counterpoint, Horowitz investigates personal, social, and political factors that actually shape the creative act. He focuses on Stravinsky, who in Los Angeles experienced a "freedom not to matter," and Dmitri Shostakovich, who was both victim and beneficiary of Soviet cultural policies. He also takes a fresh look at cultural exchange and explores paradoxical similarities and differences framing the popularization of classical music in the Soviet Union and the United States. In closing, he assesses the Kennedy administration's arts advocacy initiatives and their pertinence to today's fraught American national identity. Challenging long-entrenched myths, this book newly explores the tangled relationship between the ideology of freedom and ideals of cultural achievement"--
Foreword : why and what -- JFK, the artist, and "free societies" : a Cold War myth -- Nicolas Nabokov and the Cultural Cold War -- Lines of battle : the case for Stravinsky; the case against Shostakovich -- CIA cultural battlegrounds : New York and Paris -- Survival strategies : Stravinsky and Shostakovich -- Survival strategies : Nicolas Nabokov -- Cold War music, East and West -- Enter cultural exchange -- Summing up : culture, the state, and the "propaganda of freedom" -- Afterword : the arts, national purpose, and the pandemic.
Includes bibliographical references and index.
Description based on online resource; title from pdf title page (EBSCO, viewed on April 30, 2024).
eBooks on EBSCOhost
Keywords: Kennedy, John F. -- 1917-1963.; Shostakovich, Dmitriĭ Dmitrievich, -- 1906-1975.; Stravinsky, Igor, -- 1882-1971.; Nabokov, Nicolas, -- 1903-1978.; Congress for Cultural Freedom; Kennedy, John F. -- 1917-1963; Nabokov, Nicolas, -- 1903-1978; Shostakovich, Dmitriĭ Dmitrievich, -- 1906-1975; Stravinsky, Igor, -- 1882-1971; Congress for Cultural Freedom; Music -- Political aspects -- United States -- History -- 20th century; Music -- Political aspects -- Soviet Union -- History -- 20th century; Cold War -- Music and the war; Musique -- Aspect politique -- États-Unis -- Histoire -- 20e siècle.; Musique -- Aspect politique -- URSS -- Histoire -- 20e siècle.; MUSIC / General; Music -- Political aspects; Soviet Union; United States; Music; Music; 1900-1999; Electronic books; History